Enhancing arabic speaking skills through the chain story technique at Islamic boarding school - Nurkhamilah, Mila (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Mahārah al-kalam (Arabic speaking skills) learning at DIS Islamic Boarding School is a program implemented to enhance students' proficiency in Arabic, particularly at the Language Center. Students at the boarding school come from diverse educational backgrounds, including elementary, middle, and high school levels, with some having no prior exposure to Arabic. This diversity often leads to difficulties in mastering the language. To address this, the boarding school employs the chain story technique, a method designed to facilitate effective and accurate Arabic speaking skills. This study aims to explore the implementation of Mahārah al-kalam learning using the chain story technique at DIS Islamic Boarding School. Methods: This research adopts a qualitative descriptive approach through field research (Field Research). Data were collected using observation, interviews, and documentation techniques. The research subjects included teachers and students at DIS Islamic Boarding School. Findings: The study reveals that the chain story technique significantly enhances students' Arabic speaking skills. Students are provided with vocabulary (mufrodat) exercises every Tuesday, Wednesday, Friday, Saturday, and Sunday. Mahārah al-kalam activities are conducted weekly on Saturdays, followed by evaluations on Sundays to assess students' progress. The technique not only improves speaking skills but also integrates listening, reading, and writing abilities, creating a comprehensive and engaging learning environment. Conclusion: The chain story technique proves to be an effective method for improving Mahārah al-kalam learning, fostering students' confidence and proficiency in Arabic. Its integration of multiple language skills and interactive approach makes it a valuable tool for language education in Islamic boarding schools. Novelty/Originality of this article: This study highlights the innovative application of the chain story technique in Arabic language learning, particularly in the context of Islamic boarding schools. It provides new insights into how interactive and creative methods can address the challenges of teaching Arabic to students with diverse educational backgrounds.